Penyusunan Manajemen Pengembangan TI Agile Memakai Cobit 2019 Devops Pada Transformasi Digital Reinsurco - Cania Mustika Sundalusia; Rahmat Mulyana; Fitriyana Dewi (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2023)
The rapid advancement of digital technology, intense competition from digital rivals, and the shift in consumer behavior towards digital experiences have compelled incumbent companies to accelerate digital transformation (DT). Prior research has alrea3dy identified the influence of information technology governance (ITG) on organizational performance (OP), mediated by DT. However, a deeper exploration is still needed regarding the adoption of agile mechanisms for IT development management. A case study is conducted at ReinsurCo, utilizing the Design Science Research (DSR) method based on the ISACA COBIT 2019 DevOps Focus Area framework. Data is collected through interviews and document triangulation. Solution design and implementation roadmaps are formulated based on the assessment of seven components within two priority ITG areas at ReinsurCo: APO11 Managed Quality and BAI02 Managed Requirements Definition. The projected improvement in process capability is estimated to be 30%, reaching 2.8 if the proposed solutions are implemented. This research contributes to an enhanced understanding of agile IT development management to support DT, offering practical implications for ReinsurCo and similar companies in guiding their DT journey.